In situ solid state oxidation reaction for La1-xSrxMnO3 (x=0, 0.1, 0.2 and 0.3) formation - Marques, RFC; Jafelicci, M.; Paiva-Santos, C. O.; Varanda, L. C.; Godoi, RHM (Elsevier B.V., 2001)
In situ solid state oxidation reaction for an alternative La1-xSrxMnO3 (x = 0, 0.1, 0.2 and 0.3) formation is reported. Samples have been obtained by using strontium peroxide, lanthanum and manganese (III) oxide reagents. Strontium peroxide has induced the oxidation of Mn+3 to Mn+4. Lanthanum strontium-doped manganite was obtained without secondary phase formation. La0.825Sr0.175MnO3 showed two structural transitions. The first from 88 to 373 K and the second at 1073 K. which are explained by Jahn-Teller effect at low temperature and cation displacement at high temperature. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: lanthanum manganite; perovskite structure; phase transitions-crystallographic